Customer satisfaction towards Etiqa services provided in Kuantan Branch / Nor Asma Abu Bakar - Abu Bakar, Nor Asma (Faculty of Business and Management, 2010)
Customer satisfaction become more important as more companies strive for quality in their products and services. Hence, if the company’s perceived performance exceeds a customer’s expectations, then the customer will satisfied. On the other hand, if the company perceived performance falls short of customer’s expectation, then the customer will dissatisfied. The main purpose of this research is to study the customer’s satisfaction towards the services provided in Etiqa Kuantan. Moreover, research objectives for this study are undertaken to determine the level of customer satisfaction, to identify the relationship between customer satisfaction towards each of independent variable and to identify the most important factors that will influences customer satisfaction. A 50 set of questionnaires was distributed to the respective respondents by randomly selected. The findings showed that most of the customers were satisfied with the services provided. Customer service and Agent’s role have moderate relationship with customer satisfaction while only claim process has weak relationship. Hence, in order to improve and increase customer satisfaction, the researcher give some recommendations and suggestions after the final analysis have been made. Based on the descriptive analysis, frequency, cross tabulation and correlation from Statistical Package for Social Sciences (SPSS), a clear findings and result will be observed.